Damn Near White : An African American Family's Rise from Slavery to Bittersweet Success - Wilkins, Carolyn (Carolyn Marie) (Book collections on Project MUSE., 2010)
"Carolyn Wilkins grew up defending her racial identity. Because of her light complexion and wavy hair, she spent years struggling to convince others she was black. Her family's prominence set Carolyn's experiences even further apart from those of the average African American ... Carolyn's parents insisted she follow the color-conscious rituals of Chicago's elite black bourgeoisie--experiences Carolyn recalls as some of the most miserable of her entire life. Only in the company of her mischievous Aunt Marjory ... does Carolyn feel a true connection to her family's African American heritage. When Aunt Marjory passes away, Carolyn inherits ten bulging scrapbooks filled with family history and memories. What she finds ... inspires her to discover the truth about her ancestors--a quest that will eventually involve years of research, thousands of miles of travel, and much soul-searching ..."--Jacket